La société civile vue à l’aune de la résilience du système politique algérien - Louisa Dris-Aït Hamadouche (L’Année du Maghreb)
Since the independence of Algeria, the freedom of the Algerian civil society is inversely proportional to the welfare State strength. It is worthy noticing that this relationship did not change after instauration of pluralism and the multiplication of NGO’s. Consequently, this weak if not embryonic civil society is judged closer to a socio-political object than to a social actor. How the Algerian civil society became à part of the political system resilience? In order to answer this question, this article will decorticate some of the civil society’s characteristics through its incomplete individuals’ empowerment, its over-politicization and its openness to accept the rent redistribution. Then, it will analyze the governmental containment policy through the juridical locking, a selective demonization and division.